Educação especial inclusiva na formação continuada de docentes das licenciaturas em ciências : (re)construção de concepções e práticas - Silva, Regiana Sousa (2019)
The present thesis aimed to comprehend how a process of continued formation, addressing Inclusive Special Education, may contribute with changes in conceptions and practices of professors of Licentiate Courses in Physics, Chemistry and Biology of a Higher Education Institution. We have adopted the qualitative method, in the research-action modality, performed in three moments. In the first moment – Exploratory Phase, we tried to know which approach is being given to Inclusive Special Education in the formation of teachers in the mentioned courses of three Higher Education Institutes of São Luís – Maranhão (MA), through analysis of 9 Pedagogical Projects of Courses and of the given answers to a questionnaire by 88 teacher trainers. In the second moment, we proceeded to the collective construction of a Continued Education in Inclusive Special Education Course with the participation of 12 teacher trainers, process in which we experienced the reflective spirals, amidst the dynamics of planning, executing and evaluating. This was supported on three pillars: Classroom Training, Component Training and Online Material Study. In the third moment, also of evaluative character, we presented the results of the research to the participants. As a methodology for data analysis, we adopted the Discursive Textual Analysis of the present statements in the Pedagogical Projects of Courses and the statements of the teacher trainers presented in the questionnaires, in audiorecording transcriptions and interviews. The field diary was utilized as a means of enriching and deepening the data. In the theoretical interlocutions, we’ve dialogued with international and national documents and authors that discuss Inclusive Special Education, inclusive teaching of sciences, teacher training and teaching knowledge. The analysis of the Pedagogical Projects of Courses pointed out that the presence of the inclusive perspective in most of these documents is still due to the coercion of the legal requirement, not constituting itself as a necessary condition for the coherent formation of teachers for this century nor guiding principle in this formation. The discipline Libras (mandatory) and the discipline related to the themes of Inclusive Special Education (in some Pedagogical Projects of Courses, optional) presented programs with broad content and without relation to the specificities of the courses. The analysis of the statements of the questionnaires showed that diferent conceptions of Inclusive Education surround teacher trainers and that less than half of them claim to contribute to the training of science teachers for inclusion through the curricular component that they work with. After the realization of the Continued Formation, the understanding of the senses and meanings of the statements of the teacher trainers present in the audio-recordings and interviews point that this formation contributed to the articulation of teaching knowledge, favored the (re)construction of conceptions and practices and the comprehension that the function of training science teacher for the inclusion is a commitment of all teacher trainers, referring the thesis that the participation of teachers with degree in Physics, Chemistry and Biology in a study group, in process of continued formation in Special Education in the perspective of Inclusive Education, lined with the concept of a critical-reflexive teacher and in the sharing of pedagogical experiences, may contribute to change in their conceptions about inclusion and with changes in practice, through the construction of a new identity as professionals that train science teachers for the inclusion. In the end, suggestions are presented on the necessary knowledge to the Continued Formation of teachers in Inclusive Special Education; on characteristics that might orient the formation and on possible elements that constitute the identity of the Inclusive Teacher Trainer, aiming to contribute with the reflection and effectiveness of similar formations by other formative institutions.